Konsep Islam dan Sekularisme dalam Al-Qur’an: Analisis Tematik Terhadap Ayat-Ayat Sekularisme - Syahdani, Azka Aulia Mahara; Kusumawati, Enny; Sa’diyah, Khanifatus; Habibuddin, Wildan Hanif; Muhyi, Asep Abdul (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research aims to discuss the dynamics and challenges of secularism in various aspects of life, as well as Islam’s perspective on the concept, particularly through a thematic Qur’anic interpretation (tafsir maudhu’I This study uses a qualitative approach with library research methods, drawing on primary sources such as the Qur’an and classical exegesis, and secondary sources including academic articles and journals. The findings and discussion cover the definition of secularism, its development in politics, law, education, economy, and society, as well as the Islamic response to the ideology that separates religion from public life. The study concludes that islam is a comprehensive way of life (kaffah) that cannot be separated from worldly affairs. Islamic values remain relevant in addressing modern secular challenges. This research is expected to provide a critical understanding of the impact of secularism in Muslim societies. However, It is limited by the lack of empirical data on the actual implementation of secularism in Muslim-majority countries. Therefore, further research is needed to explore more practical and contextual approaches to the role of religion is modern public life.